GAMIFICATION CONCEPT OF FIVE SENSES IN LEARNING RECEPTIVE LANGUAGE SKILL IN THE GERMAN LANGUAGE EDUCATION STUDY PROGRAM - Lestuny, Caroline; Soumokil, Piet (Pattimura University, 2023)
Fun learning has an impact on students and lecturers. To create fun learning, it is necessary to have a game concept which contributes in learning. Gamification is not a new thing in the learning process but an important part that needs to be implemented. Receptive language skill is a subject with two language skills namely reading comprehension (Lesen) and listening comprehension (Hören). The learning process that is being carried out is quite boring because of boredom and difficulties in understanding written texts and audio texts. This research was conducted with the aim of knowing the application and perceptions of students about the concept of gamification